Small Bowel Obstruction Secondary to Intussuscepted Meckel’s Diverticulum in an Adult - Daniel John Marascia (Case Reports in Surgery)
Intussusception secondary to inverted Meckel’s diverticulum resulting in intestinal obstruction is rare. The following is a case report that discusses a 29-year-old female who posed diagnostic uncertainty for the treating surgical team and ultimately underwent emergency surgery for the management of intestinal obstruction. Small bowel intussusception was diagnosed preoperatively on abdominal computer tomography (CT). At operation, it was found to be secondary to inverted Meckel’s diverticulum with histopathology confirming the diagnosis.